Time to look forward: advocating future orientation in business network research - Halinen Aino; Nordberg-Davies Sini; Möller Kristian (Emerald, 2025)
Purpose - Future is rarely explicitly addressed or problematized in business network research. This study aims to examine the possibilities of developing a business actor's future orientation to network studies and imports ideas and concepts from futures research to support the development.
Design/methodology/approach - The study is conceptual and interdisciplinary. The authors critically analyze how extant studies grounded in the sensemaking view and process research approach integrate future time and how theoretical myopia hinders the adoption of a future orientation.
Findings - The prevailing future perspective is restricted to managers' perceptions and actions at present, ignoring the anticipation and exploration of alternative longer-term futures. Future time is generally conceived as embedded in managers' cognitive processes or is seen as part of the ongoing interaction, where the time horizon to the future is not noticed or is at best short.
Research limitations/implications - To enable a forward-looking perspective, researchers should move the focus from expectation building in business interaction to purposeful preparation of alternative future(s) and from the view of seeing future as enacted in the present to envisioning of both near-term and more distant futures.
Practical implications - This study addresses the growing need of business actors to anticipate future developments in the rapidly changing market conditions and to innovate and change business practices to save the planet for future generations.
Originality/value - This study elaborates on actors' future orientation to business markets and networks, proposes the integration of network research concepts with concepts from futures studies and poses new types of research questions for future research.